Inflation and income distribution in Brazil from a Kaleckian perspective - Lilian Rolim (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
This article shows that income inequality and inflation in Brazil are multidimensional phenomena linked to the unemployment rate and to the foreign sector. Consequently, the relationship between inflation and income distribution depends on the source of inflationary pressures, as evident in the 2000 to 2020 period. This reflects significant differences in the dynamics of inflation in the tradable and non-tradable goods sectors and is consistent with the Kaleckian framework. Yet, a missing inequality puzzle is identified, suggesting that changes in the Industry sector's relation with the foreign sector altered some of the relationships analyzed. The article also investigates the influence of the foreign sector on the intensity of the domestic distributive conflict in Brazil and discusses some implications of an intensified distributive conflict in terms of policies and regulations that alter the bargaining power of workers.
Keywords: D33; E31; E52; 330; Distributive conflict; Foreign sector; Income inequality; Inflation-targeting regime; Phillips curve